(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 20:27:10
(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0
(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6
(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6
(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6
(0.4x-2.1)/0.5=(0.1+0.2x)/0.03-0.6
(4x-21)/5=(10+20x)/3-0.6
3(4x-21)=5(10+20x)-9
12x-63=50+100x-9
12x-100x=41+63
-88x=104
-22x=26
x=-13/11
(4x-21)/5=(10+20x)/3-3/5
3(4x-21)=5(10+20x)-9
12x-63=50+100x-9
-88x=104
x=-13/11
(4x-21)/5=(10+20x)/3-3/5
3(4x-21)=5(10+20x)-9
12x-63=50+100x-9
-88x=104
x=-13/11